The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1126/sciadv.abe3706
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide prevents aortic valve calcification by S-nitrosylation of USP9X to activate NOTCH signaling

Abstract: Calcific aortic valve disease (CAVD) is an increasingly prevalent condition, and endothelial dysfunction is implicated in its etiology. We previously identified nitric oxide (NO) as a calcification inhibitor by its activation of NOTCH1, which is genetically linked to human CAVD. Here, we show NO rescues calcification by an S-nitrosylation–mediated mechanism in porcine aortic valve interstitial cells and single-cell RNA-seq demonstrated NO regulates the NOTCH pathway. An unbiased proteomic approach to identify … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 59 publications
(85 reference statements)
1
64
1
Order By: Relevance
“…Endothelial-derived NO inhibits calcification of porcine aortic VICs in vitro and modulates Notch1 signalling ( 74 ). Post-translational modification of the deubiquitinase USP9X has been demonstrated as a mechanism for NO-mediated inhibition of myofibroblastic porcine aortic VIC differentiation ( 75 ). In models of vascular calcification, endothelial-derived NO inhibits TGFβ signalling in vascular smooth muscle cells, which may be an additional mechanism by which NO signalling inhibits pathological VIC differentiation ( 76 ).…”
Section: The Role Of Valvular Endothelial Cells In Development Of Cal...mentioning
confidence: 99%
“…Endothelial-derived NO inhibits calcification of porcine aortic VICs in vitro and modulates Notch1 signalling ( 74 ). Post-translational modification of the deubiquitinase USP9X has been demonstrated as a mechanism for NO-mediated inhibition of myofibroblastic porcine aortic VIC differentiation ( 75 ). In models of vascular calcification, endothelial-derived NO inhibits TGFβ signalling in vascular smooth muscle cells, which may be an additional mechanism by which NO signalling inhibits pathological VIC differentiation ( 76 ).…”
Section: The Role Of Valvular Endothelial Cells In Development Of Cal...mentioning
confidence: 99%
“…Indeed, NO synthesis and signaling are markedly affected by the oscillatory shear stress in the endothelium lining the calcification-prone fibrosa compared with the disease-resilient ventricularis [ 25 ]. In vivo studies have shown that a lack of eNOS in mice promotes a CAVD-like phenotype [ 26 ], whereas restoring paracrine NO signaling blunts VIC-driven calcification in different experimental models [ 27 ]. Furthermore, studies have also reported that NO maintains valvular homeostasis through guanylyl cyclase/cGMP- and NOTCH1-dependent mechanisms [ 28 , 29 ].…”
Section: Role Of Lipoprotein(a) and Oxidized Phospholipids In Cavdmentioning
confidence: 99%
“…Increasing NO bioavailability not only reduces the burden of ROS but also regulates Notch1 signalling and its nuclear localization to reduce the expression of osteogenic markers in VICs. 283 , 284 …”
Section: Targeting Ros In Cavdmentioning
confidence: 99%